Efforts to Improve Students' Understanding in Learning Mathematics Through the RME Approach - Nita Anggriya Lawati; Cahya Hatia Ananda (Journal of Contemporary Islamic Primary Education, 2022)
This article aims to find out how learning mathematics in the "Bangun Datar" material with the RME (Realistic Mathematika Education) approach improves students' mathematics learning outcomes using the RME approach on data building material. The instrument used in this study is observing the steps in the RME approach, namely relating, experiencing, applying, Cooperating, and Transferring. At this time, RME supports learning mathematics in "flat-up" material. With this approach, students are expected to be able to be active in the RME system or approach in the learning process. In this learning, students think creatively, because mathematics provides new information for students in understanding the concept of "flat wake".